Advancing next-generation brain organoid platforms for investigating traumatic brain injury from repeated blast exposures - Bar-Kochba, Eyal; Carneal, Catherine M.; Alphonse, Vanessa D.; Timm, Andrea C.; Ernlund, Amanda W.; Rodriguez, Carissa L.; Morales Pantoja, Itzy E.; Smirnova, Lena; Hartung, Thomas; Merkle, Andrew C. (Frontiers in Bioengineering and Biotechnology, 2025)
Service members and law enforcement personnel are frequently exposed to blast overpressure during training and combat due to the use of heavy weaponry such as large-caliber rifles, explosives, and ordnance. The cumulative effects of these repeated low-level (<4 psi) blast exposures can lead to physical and cognitive deficits that are poorly understood. Brain organoids—human stem cell-derived three-dimensional in vitro culture systems that self-organize to recapitulate the in vivo environment of the human brain—are a promising alternative biological model to traditional cellular cultures and animal models, offering a unique opportunity for studying the mechanisms of mild blast-induced traumatic brain injury (mbTBI) resulting from repeated exposure. In this article, we review the current state of brain organoid models and discuss future directions for advancing their physiological relevance for studying mbTBI. These will be presented within a framework for developing next-generation platforms that integrate relevant loading devices, as well as non-invasive technologies for assessing the brain organoid’s response while increasing throughput. These next-generation platforms aim to accelerate the development of new interventions for mbTBI.